2004
DOI: 10.1002/mats.200300050
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Step Interval and Modified Rosenbrock Method for Kinetic Parameter Estimation in Copolymerization Systems: A Robust and Reliable Approach

Abstract: Summary: The kinetics of solution free radical copolymerization of isobutyl methacrylate (i‐BMA) and lauryl methacrylate (LMA) in benzene, initiated with 2,2‐azoisobutyronitrile (AIBN) were studied at different monomer feed compositions at low conversion levels. In order to avoid the complications of copolymerization kinetics, the pseudo‐kinetic rate constant method was applied in constant and variable volume polymerization systems. A two‐step procedure based on interval analysis and the modified Rosenbrock me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Also, the values of the coupled rate parameter, k p / k t 0.5 , at different monomer feed compositions were estimated and are shown in Figure 7. The solid line in this figure shows the prediction of the implicit penultimate unit model (IPUM) of Fukuda and coworkers44, 45 with the reactivity ratios previously reported by Habibi and Vasheghani‐Farahani 43…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Also, the values of the coupled rate parameter, k p / k t 0.5 , at different monomer feed compositions were estimated and are shown in Figure 7. The solid line in this figure shows the prediction of the implicit penultimate unit model (IPUM) of Fukuda and coworkers44, 45 with the reactivity ratios previously reported by Habibi and Vasheghani‐Farahani 43…”
Section: Resultssupporting
confidence: 53%
“…Because the induction period represents the required time for the consumption of primary radicals, its measurement provides a direct calculation of the in situ initiation rates. f was previously determined43 by the mean kinetic chain length approach and was equal to 0.62. It was assumed that the efficiency of initiation was constant and was not influenced by the presence of the inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…6a. The solid line in this figure is the prediction of Implicit Penultimate Unit Model (IPUM) of Fukuda et al (1985Fukuda et al ( , 1992 using the previously reported reactivity ratios by Habibi and Vasheghani-Farahani (2004). Also the estimated values of 2fk d at different monomer feed compositions are shown in Fig.…”
Section: Inhibited Polymerizationmentioning
confidence: 97%
“…The initiator efficiency, f which was previously determined by the "Mean kinetic chain length" method (Habibi and Vasheghani-Farahani, 2004) is set to 0.62. It is assumed that the efficiency of initiation is constant and not influenced by the presence of inhibitor.…”
Section: Inhibited Polymerizationmentioning
confidence: 99%
“…Based on the values of elementary rate constants, [67] a couple of MCMC simulations were performed. All elementary reactions (i.e., initiation, propagation, termination by combination, termination by disproportionation and transfer) were considered in the simulation.…”
Section: Prediction Of Species and Copolymerization Ratementioning
confidence: 99%